Experimental investigation on longitudinal and transverse temperature distribution in a horseshoe shaped tunnel fire. Issue 9 (July 2019) - Gao, Yunji; Zhu, Guoqing; Gu, Sinian; Zhu, Hui; An, Weiguang
The longitudinal temperature distribution in a tunnel fire has been investigated wildly as the classical problem, while the transverse temperature distribution, especially sidewall temperature, has not received adequate attention. In this article, a 1:3.7 reduced scale horseshoe shaped model tunnel constructed by concrete was established, in which a series of comparative burning experiments were carried out to investigate the longitudinal and transverse temperature distributions. The quantitative trends of smoke longitudinal and transverse temperature including sidewall temperature were observed and analyzed. The major conclusions are summarized as follows: The temperature rise under the ceiling first decreases sharply with longitudinal distance from fire source, followed by a slight decrease, which can be well predicted by Gong's model of a sum function of two exponential equations. The transverse temperature rise in fire zone is dominated by two different heat transfer regions: convection region (angle below 45° or dimensionless angle below 0.8) and radiation region (angle beyond 45° or dimensionless angle beyond 0.8). The inclination angle is the angle between center line of tunnel and connection line of thermocouple with fire source. The transverse temperature drops with angle in convection region and rises in radiation region, which can be well described by proposed empirical exponential functions. The non-monotonic variation trend of transverse temperature distribution in fire zone is a result of competition between convection of hot smoke and radiation of fire source. All these results are significantly important for fire safety design of tunnel and fire hazard evaluation of tunnel fire.